Digital Marketing for MSMEs and Farmer Groups in the District of Kamang Magek: Marketing Digital bagi UMKM dan Kelompok Tani di Kecamatan Kamang Magek - Hera Dwi Triani; Vitriani; Budhi Mulyadi; Mitra; Gressy Novita; Veronika; Hendrawati; Gusmulyani; Suryani (Journal of Community Service and Application of Science, 2022)
In today's digital era, information technology is developing rapidly. This technological development requires all lines of life to adapt to the use and utilization of information and communication technology, including the MSME sector (Micro, Small and Medium Enterprises). The success rate of adapting to the MSME sector greatly influences the success of MSME in dominating the market and reaching consumers according to the MSME target, where sales volume is also heavily influenced by digital marketing strategies. Digital marketing has a big role for MSMEs in providing information, facilitating direct interaction with consumers, and expanding market reach both nationally and internationally so that MSME sales can increase. However, in reality there are still many MSMEs who do not understand digital marketing, especially MSMEs in Kamang Magek District. The problems that occur at this time include marketing problems and determining the selling price, MSME actors and farmer group businesses do not have a good market so many of them sell their products and business results to middlemen or collectors where the selling price is often not proportional to the price of production, many MSME actors who are not independent and depend on middlemen or collectors to sell their products or business results. This Community Service aims to provide knowledge and understanding to MSME actors regarding the importance of digital marketing for marketing their businesses by utilizing social media. The methods of community service activities are lectures, discussions and direct training for MSME actors